Evaluating a graduate program of English language teacher education - Keşli Dollar, Yeşim; Tekiner, Aylin; Doyran, Feyza (My University, 2014)
This study evaluated the MA-TEFL Program at a foundation university. It focuses on strengths and weaknesses of the program and how much the program satisfies and meets the needs of the graduate studentstending to work as teacher trainers.The data was collected from the students, the professors, the administrators, and the graduates through a survey, interviews, and document analysis of the curriculum, course syllabi and materials. Qualitative data analysis techniques were used to identify the strengths, weaknesses of the program, and the students’ needs. This study illuminated new student needs which were not taped into. To meet students’ needs better, this program will be modified and proposed to the Council of Higher Education.

Bu çalışma bir vakıf üniversitesindeki İngilizce Öğretmenliği Yüksek Lisans programını değerlendirmeyi amaçlamaktadır. Çalışma, programıngüçlüvezayıfyönlerine odaklanarak lisansüstü öğrencilerinin programdan memnun olup olmadıklarını bulmayı hedeflemiştir.Bu çalışmada, öğrenciler, öğretim üyelerive program koordinatörü yer almışlardır. Dönem başında öğrencilere ve öğretim üyelerine programla ilgili düşüncelerini ölçen bir anket uygulanmıştır. Akademik yılın sonunda ise öğrenciler ders değerlendirmesi yapmışlardır. Ayrıca, ders materyalleri, ders izlenceleri, ölçme ve değerlendirmede kullanılan materyaller ve program müfredatı araştırmacılar tarafından incelenmiştir. Nitel araştırma teknikleri kullanılarak veriler analiz edilmiştir. Sonuç olarak, programın güçlü yönlerive geliştirilebilecek yönleri tespit edilmiştir ve öğrencilerin ihtiyaçlarını daha iyi karşılayacak yüksek lisans programının yeniden düzenlenmiş hali YÖK’ e sunulacaktır.
İngiliz dili eğitimi yüksek lisans programı değerlendirmesi
Keywords: English Language Teaching; Course Evaluation; Program Evaluation; Teacher Education; İngiliz Dili Öğretimi; Ders Değerlendirmeleri; Program Değerlendirme; Öğretmen Eğitimi